The Flp type IV pilus operon of Mycobacterium tuberculosis is expressed upon interaction with macrophages and alveolar epithelial cells - Alteri, Christopher J.; Rios-Sarabia, Nora; De la Cruz, Miguel A.; González-y-Merchand, Jorge A.; Soria-Bustos, Jorge; Maldonado-Bernal, Carmen; Cedillo, María L.; Yáñez-Santos, Jorge A.; Martínez-Laguna, Ygnacio; Torres, Javier; Friedman, Richard L.; Girón, Jorge A.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The genome of Mycobacterium tuberculosis (Mtb) harbors the genetic machinery for assembly of the Fimbrial low-molecular-weight protein (Flp) type IV pilus. Presumably, the Flp pilus is essential for pathogenesis. However, it remains unclear whether the pili genes are transcribed in culture or during infection of host cells. This study aimed to shed light on the expression of the Flp pili-assembly genes (tadZ, tadA, tadB, tadC, flp, tadE, and tadF) in Mtb growing under different growth conditions (exponential phase, stationary phase, and dormancy NRP1 and NRP2 phases induced by hypoxia), during biofilm formation, and in contact with macrophages and alveolar epithelial cells. We found that expression of tad/flp genes was significantly higher in the stationary phase than in exponential or NRP1 or NRP2 phases suggesting that the bacteria do not require type IV pili during dormancy. Elevated gene expression levels were recorded when the bacilli were in contact for 4 h with macrophages or epithelial cells, compared to mycobacteria propagated alone in the cultured medium. An antibody raised against a 12-mer peptide derived from the Flp pilin subunit detected the presence of Flp pili on intra- and extracellular bacteria infecting eukaryotic cells. Altogether, these are compelling data showing that the Flp pili genes are expressed during the interaction of Mtb with host cells and highlight a role for Flp pili in colonization and invasion of the host, subsequently promoting bacterial survival during dormancy.